THE INFLUENCE OF PERSONALITY TYPE ON FOREIGN LANGUAGE LEARNING: A CRITIQUE OF THE ACCELERATIVE INTEGRATED METHOD - Poonoosamy, Mico (PEOPLE: International Journal of Social Sciences, 2019)
The Accelerative Integrated Method (AIM) is an inductive approach to second language acquisition. It was developed in Canada in 1999 by Wendy Maxwell to teach French in primary school. The AIM is currently being used to teach also English, Spanish, Mandarin and Japanese in over 10,000 primary and secondary schools in the world. The method privileges meaning-making and effective communication through a gesture approach. Maxwell claims that the AIM allows learners to reach high levels of communicative proficiency quickly, mainly through an emotional engagement with the language that they learn through dance, drama and creative writing. This paper critically evaluates the AIM; it focuses on how much it draws and impacts on the learner’s personality. It also explores the appropriateness of the AIM for secondary school students who have a higher cognitive developmental age than primary students for whom the AIM was originally designed. The discussion is informed by theories on second language acquisition, emotion and personality type. The paper concludes by making recommendations on learning and teaching methodologies that can challenge and successfully engage foreign language learners while also developing in them intercultural literacy.